1996
DOI: 10.1111/j.0953-0673.1996.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response of omeprazole combined with amoxycillin on duodenal ulcer healing and eradication of Helicobacter pylori.

Abstract: Combination of either omeprazole 20 or 40 mg b.d. plus amoxycillin 1 g b.d., is not sufficiently effective to be recommended as an anti-H. pylori therapy. Omeprazole 80 mg b.d. combined with amoxycillin is more efficient and well tolerated, but better treatment options now exist to cure H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Interestingly, smoking did not affect the outcome of dual therapy in this study. This ®nding is in line with the study by Pommerien et al 18 but in contradiction to the results reported by others. 15,16,21,33,34 In conclusion, increasing the dose of omeprazole in dual therapy with amoxycillin improves the cure of H. pylori infection.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, smoking did not affect the outcome of dual therapy in this study. This ®nding is in line with the study by Pommerien et al 18 but in contradiction to the results reported by others. 15,16,21,33,34 In conclusion, increasing the dose of omeprazole in dual therapy with amoxycillin improves the cure of H. pylori infection.…”
Section: Discussionsupporting
confidence: 67%
“…This international, randomized, double-blind multicentre study with parallel groups has shown that doubling the dose of omeprazole (40 mg 18 From the results of these high quality studies and a further dose-®nding study, 19 it can be concluded that omeprazole 40± 80 mg/day combined with amoxycillin 1.5±2 g/day cures H. pylori infection in about 50±60% of ulcer patients, with the higher dose of omeprazole being more effective. Increasing the dose of omeprazole to 120 mg or more will probably improve the treatment results.…”
Section: Discussionmentioning
confidence: 98%
“…In dual therapy, omeprazole in a daily dose of 80 mg combined with amoxycillin (1 g b.d.) for 14 days was more effective in eradication of H. pylori than in the daily doses of 20 or 40 mg. 18 Similarly, a dual therapy based on a higher (2´40 mg) dose of omeprazole in association with amoxycillin gave a higher eradication rate (60%) in H. pylori-positive ulcer patients than the same therapy based on a lower (2´20 mg) dose of this proton pump inhibitor (37%). 19 In triple therapy with amoxycillin and metronidazole, lansoprazole in a double dose (60 mg o.d.)…”
Section: Discussionmentioning
confidence: 99%
“…The addition of higher doses of ranitidine or omeprazole to amoxicillin has been reported to give eradication rates of approximately 60% 47 . Several studies have suggested that high doses of omeprazole increase the concentration of amoxicillin in the gastric juice, 54 and that a higher dose of the proton pump inhibitor improves the eradication rate of dual therapy with proton pump inhibitor and amoxicillin 55–58 …”
Section: Discussionmentioning
confidence: 99%